2016
DOI: 10.1042/cs20150666
|View full text |Cite
|
Sign up to set email alerts
|

Emerging importance of chemokine receptor CXCR3 and its ligands in cardiovascular diseases

Abstract: The CXC chemokines, CXCL4, -9, -10, -11, CXCL4L1, and the CC chemokine CCL21, activate CXC chemokine receptor 3 (CXCR3), a cell-surface G protein-coupled receptor expressed mainly by Th1 cells, cytotoxic T (Tc) cells and NK cells that have a key role in immunity and inflammation. However, CXCR3 is also expressed by vascular smooth muscle and endothelial cells, and appears to be important in controlling physiological vascular function. In the last decade, evidence from pre-clinical and clinical studies has reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 153 publications
3
68
0
1
Order By: Relevance
“…Using in silico target prediction analysis and luciferase reporter assays, we observed that PDLIM1 was the target gene most significantly upregulated in the BMDMs of miR-150 / ApoE / mice and that PDLIM1 luciferase activity was enhanced by miR-150 inhibitor transfection; however, these changes were prevented by the mutation of the predicted binding sites within the PDLIM1 3′UTR. Moreover, we noted that CXCL3 and CXCL2, which play important roles in macrophage recruitment and plaque progression (39)(40)(41), were downregulated in the BMDMs of miR-150 / ApoE / mice. In a previous study, PDLIM1 decreased phosphorylated p65 expression and attenuated pro-inflammatory cytokine/chemokine secretions (42).…”
Section: Discussionmentioning
confidence: 86%
“…Using in silico target prediction analysis and luciferase reporter assays, we observed that PDLIM1 was the target gene most significantly upregulated in the BMDMs of miR-150 / ApoE / mice and that PDLIM1 luciferase activity was enhanced by miR-150 inhibitor transfection; however, these changes were prevented by the mutation of the predicted binding sites within the PDLIM1 3′UTR. Moreover, we noted that CXCL3 and CXCL2, which play important roles in macrophage recruitment and plaque progression (39)(40)(41), were downregulated in the BMDMs of miR-150 / ApoE / mice. In a previous study, PDLIM1 decreased phosphorylated p65 expression and attenuated pro-inflammatory cytokine/chemokine secretions (42).…”
Section: Discussionmentioning
confidence: 86%
“…Emerging evidence has shown that chemokines play a critical role in early myocardial dysfunction and disease progression following MI by regulating infarct angiogenesis, leukocyte infiltration and fibrous tissue deposition252627. The infarct size can be reduced and cardiomyocyte injury can be prevented by targeting chemokine-mediated inflammation in the post-MI heart282930313233.…”
Section: Discussionmentioning
confidence: 99%
“…CCL26 was unique in that its level was significantly diminished before TX and saw a significant elevation in a large number of patients after transplant to the extent that in all post-TX patients, CCL26 was uniquely elevated above the upper pre-TX level. This central finding suggests that there may be a biological relevance to this molecule in transplant immunobiology [40, 41]. Interestingly, this chemokine uses-receptor that is present on eosinophils, basophils, T helper 2, monocytes, dentritic cells, plasma cells and natural killer cells.…”
Section: Discussionmentioning
confidence: 99%